THE EFFECT OF THE USING OF EXTRACTION SOLUTIONHClAT DIFFERENT CONCENTRATIONS ON THE MINERAL CONTENT OF BLACK SEA CUCUMBAR (Holothuria edulis) - Roy Susanto; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of the research was to know the effect of the using of HCl at the different concentrations on the extraction of the mineral content of black sea cucumber (Holothuria edulis). The design used was completely randomized design (CRD). The treatment conducted was consisting of three varied concentrations of HCl, namely: P1 (HCl with concentration of 4%), P2 (HCl with concentration of 5%), and P3 (HCl with concentration of 6%). The results showed that the black sea cucumber contained moisture of(86,42%), ash of (3,94%), fat of (0,83%), protein of (7,87%), carbohydrate of (0,94%), calcium of (6,82 mg/100), potassium of (1,04 mg/100), sodium of (9,51 mg/100), magnesium of (11,90 mg/100), phosphor of (0,31 mg/100), and the iron of (4,02 mg/100).Keywoard: Black sea cucumber, Hydrochloric acid, Mineral